Lamotrigine Open Trial in Refractory Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Lamotrigine, 5 and 15 mg/kg/daily, was administered as add-on therapy in 37 outpatient children and adolescents with refractory epilepsy and mental delay treated at the Child Neuropsychiatry Unit, Department of Pediatrics, Second University of Naples, Italy.